Hypofractionation with simultaneous integrated boost after breast-conserving surgery: Long term results of two phase-II trials. (August 2022) - Pfaffendorf, Charlotte; Vonthein, Reinhard; Krockenberger-Ziegler, Katja; Dellas, Kathrin; Schreiber, Andreas; Uhlemann, Dorit; Dinges, Stefan; Würschmidt, Florian; Andreas, Peter; Weinstrauch, Evelyn; Eilf, Kirsten; Rades, Dirk; et al.
Abstract: Purpose: To analyze long-term results of two multicenter prospective single-arm trials (ARO-2010-01 and ARO-2013-04) investigating adjuvant hypofractionated radiotherapy (HF) with simultaneous integrated boost (SIB) after breast-conserving surgery (BCS). Methods: Eligible patients had histopathologically confirmed unifocal breast cancer planned for whole breast irradiation plus boost radiotherapy to the tumor bed. In both studies, a total dose of 40 Gy was applied to the whole breast and of 48 Gy to the tumor bed in 16 fractions of 2.5 and 3.0 Gy. Radiotherapy could be given either as three-dimensional conformal radiotherapy (3D-CRT) or as intensity-modulated radiotherapy (IMRT). The primary study objectives were feasibility and security within an observation period of six months. The current investigation focuses on long-term efficacy and toxicities. Results: Between 2011 and 2014, both trials enrolled 300 patients in total. Data from 274 of these patients could be used for the current analysis. The median follow-up time was 60 months and the 5-year disease-free survival 92.1%. Three patients suffered a local recurrence (after 36–72 months) while a regional recurrence occurred in one patient (after 17 months). The 5-year local control rate in the breast was 99.6%. 63.5% of all patients did not report any late radiation-related toxicity, 28.5% reported grade 1 and 7.3% grade 2 toxicities. The highest late toxicity was grade 3 in 2 women (0.7%, telangiectasia and lymphedema of the breast). Conclusion: Our analysis demonstrates favorable efficacy and low rates of long-term side effects of HF with SIB after BCS. Randomized controlled phase III trials are ongoing. Highlights: Hypofractionated breast radiotherapy with SIB was safe and feasible. The local control rate at 5 years was 99.6%. The rate of late grade 3 toxicity was 0.7%.